TINJAUAN YURIDIS PENGHAPUSAN PIDANA MATI DARI PEMIDANAAN DI INDONESIA (Studi Putusan Mahkamah Konstitusi Nomor 2-3/PUU-V/2017) - Asri Evanggeline Silalahi; Evi Deliana; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The right to life is protected by a constitution that is imbued with humanity in Pancasila, but to date the Indonesian legal system still applies to the death penalty. This is in contradiction with the concept of humanity in Pancasila. The right to life is a category of rights that cannot be violated, reduced, and limited under any circumstances, including within the limits of formal regulations because the Constitution of the Republic of Indonesia is the highest provision in a state of law in Indonesia and no other provisions who can rule it out. The purpose of writing this thesis, namely; First, to find out whether capital punishment is still relevant to be maintained in the Criminal Code and other laws and regulations in Indonesia, Second, to find out the ideal concept of fulfilling human rights related to capital punishment in the Unitary State of the Republic of Indonesia.This type of research is normative legal research, library law research by conducting the study of legal principles. Data sources used in this study are secondary data, namely data obtained from literature such as legal journals, books, judges' decisions related to research. This data analysis is done qualitatively and deductive conclusions are drawn.From the research results there are two main problems that can be concluded. First, Indonesia is a country that still adheres to the death penalty in its positive law. Capital punishment is no longer relevant to be maintained in the new National Criminal Code in Indonesia or the provisions of regulations outside the Criminal Code, because capital punishment is contrary to the souls that exist in the 1945 Constitution of the Republic of Indonesia and Law Number 39 of 1999 concerning Human Rights and besides that capital punishment shows the inability of the state to educate prisoners in a better direction. Second, the protection, promotion, enforcement and fulfillment of human rights are the responsibility of the state, especially the Government. Life sentence in moral, physical and psychological terms is far more severe than a death sentence. The government must draft a Criminal Law in accordance with the constitutional directives and a number of Human Rights Laws, one of which is to revoke articles containing the death penalty.Keywords: Death Penalty, Human Rights